Predictors of Treatment Resistance and Relapse in Antineutrophil Cytoplasmic Antibody–Associated Small-Vessel Vasculitis: Comparison of Two Independent Cohorts - Pagnoux, Christian (2008)
OBJECTIVE: Predictors of treatment resistance and relapse have been identified in patients with antineutrophil cytoplasmic antibody (ANCA)–associated vasculitis in the Glomerular Disease Collaborative Network (GDCN) in the southeastern US. This study was undertaken to evaluate the applicability of those predictors in an independent cohort followed up by the French Vasculitis Study Group. METHODS: Predictors of treatment resistance were evaluated using logistic regression models and reported as odds ratios (ORs) with 95% confidence intervals (95% CIs). Predictors of relapse were evaluated using Cox proportional hazards models and reported as hazard ratios (HRs) with 95% CIs. Models were controlled for age, sex, race, baseline serum creatinine level, and cyclophosphamide therapy. RESULTS: The French cohort (n = 434) and the GDCN cohort (n = 350) had similar median followup periods (44 months versus 45 months) and initial percentages of patients taking cyclophosphamide (82% versus 78%). The French cohort included more patients with proteinase 3 (PR3) ANCA (58% versus 40%), lung involvement (58% versus 49%), and upper respiratory tract involvement (62% versus 31%). Of the predictors of treatment resistance in the GDCN cohort (female sex, African American race, presence of myeloperoxidase ANCA, elevated creatinine level, and age), only age predicted treatment resistance in the French cohort (OR 1.32 per 10 years [95% CI 1.05–1.66]). Predictors of relapse in the GDCN cohort were PR3 ANCA (HR 1.77 [95% CI 1.11–2.82]), lung involvement (HR 1.68 [95% CI 1.10–2.57), and upper respiratory tract involvement (HR 1.58 [95% CI 1.00–2.48]), while predictors in the French cohort were PR3 ANCA (HR 1.66 [95% CI 1.15–2.39]) and lung involvement (HR 1.56 [95% CI 1.11–2.20]), but not upper respiratory tract involvement (HR 0.96 [95% CI 0.67–1.38]). CONCLUSION: Our findings indicate that older age is a predictor of treatment resistance, and that PR3 ANCA and lung involvement are predictors of relapse in both cohorts. Discrepancies in predictors of treatment tract resistance may reflect differences in access to care, and differences in predictors of relapse may reflect variations in disease expression.